PELAKSANAAN PROGRAM PENDIDIKAN DAN PELATIHAN KERJA OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Kiki Dwi Jasmi; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to determine the implementation of educational programs and job training and what are the inhibiting factors. The problem in this study is that the percentage of local labor absorption is still low, not all job seekers can join this program because of the participant quota restrictions, there is no follow-up to this program, such as in the distribution of labor to companies to participants, the guidance process is not optimal, there are limited facilities and infrastructure, no permanent teaching staff. This study uses a descriptive qualitative research method with a phenomenological approach. While the data collection technique uses the method of observation, interviews, and documentation. The results showed that the implementation of the education and job training programs carried out by the Department of Manpower and Transmigration of Bengkalis Regency had not run optimally. This is because there are indicators of implementation that have not been going well, besides that there are also inhibiting factors in their implementation, including limited budget, facilities and infrastructure.Keywords: Implementation, Program, Education and Training